(untitled) (Bangladesh Journal of Zoology, 2017)
A study on the crab-spiders was carried out from different areas of Bangladesh. Two species of the genus Camaricus Thorell were recorded during the study, of which one species Camaricus chayani nov. sp. is reported to be new to science and other one C. formosus Thorell is a new record for the area of present study. The paper contains generic diagnosis, illustrated description and distribution together with key to the species. Bangladesh J. Zool. 44(2): 255-265, 2016